Towards More Sustainable Aqueous Zinc‐Ion Batteries - Zhu, Jiacai; Tie, Zhiwei; Bi, Songshan; Niu, Zhiqiang (Angewandte Chemie International Edition, 2024)
Aqueous zinc‐ion batteries (AZIBs) are considered as the promising candidates for large‐scale energy storage because of their high safety, low cost and environmental benignity. The large‐scale applications of AZIBs will inevitably result in a large amount of spent AZIBs, which not only induce the waste of resources, but also pose environmental risks. Therefore, sustainable AZIBs have to be considered to minimize the risk of environmental pollution and maximize the utilization of spent compounds. Herein, this minireview focuses on the sustainability of AZIBs from material design and recycling techniques. The structure and degradation mechanism of AZIBs are discussed to guide the recycling design of the materials. Subsequently, the sustainability of component materials in AZIBs is further analysed to pre‐evaluate their recycling behaviors and mentor the selection of more sustainable component materials, including active materials in cathodes, Zn anodes, and aqueous electrolytes, respectively. According to the features of component materials, corresponding green and economic approaches are further proposed to realize the recycling of active materials in cathodes, Zn anodes and electrolytes, respectively. These advanced technologies endow the recycling of component materials with high efficiency and a closed‐loop control, ensuring that AZIBs will be the promising candidates of sustainable energy storage devices. This review will offer insight into potential future directions in the design of sustainable AZIBs. Aqueous zinc ion batteries (AZIBs) generally display high safety and environmental friendliness. However, their large‐scale applications will generate huge amounts of depleted batteries, leading to environmental concern and resource waste. Therefore, the sustainability of AZIBs have to highly considered. This minireview aims to make AZIBs more sustainable from the focus on material design and their recycling techniques, including active materials in cathodes, Zn anodes, and aqueous electrolytes.